Ensayo de micronúcleos como herramienta para evaluar el daño genotóxico en personas expuestas a plaguicidas: Revisión Sistemática - Bravo Espinosa, Freddy Andrés (2023)
The increasing use of pesticides in agriculture has increased farmers' exposure to potential mutagens. These chemical agents can cause genotoxic damage, posing a risk to human health and the environment. Biomarkers are biological measurements that reflect the interaction between a potentially hazardous environmental agent and a biological system. In the context of farmers exposed to pesticides, the micronucleus test is relevant as an indicator of possible alterations in the genetic material. An exhaustive systematic review was carried out in order to evaluate the micronucleus assay, selecting studies from 2018 that indicate the prevalence of micronuclei in populations exposed to pesticides and compare it with non-exposed groups. In addition to this, studies that relate the appearance of micronuclei with other scenarios of cytogenetic damage, this in order to determine the usefulness of this biomarker. 18 articles were analyzed, including 15 cross-sectional studies and 3 systematic reviews and meta-analyses, in which it was observed that there was statistically significant evidence demonstrating an association between greater exposure to pesticides and the greater frequency of appearance of micronuclei. Furthermore, a greater frequency of these biomarkers was evident in pathologies associated with damage to the DNA of cells. In conclusion, the micronucleus assay can be used as a precise and effective tool to evaluate the impact of exposure to pesticides on occupational and environmental health, which will allow preventive measures to be taken to protect farmers and the ecosystem